Treatment of Pruritus Secondary to Liver Disease - Düll, Miriam; Kremer, Andreas (Current Gastroenterology Reports, 2019)
Purpose of Review: Pruritus is a common extrahepatic symptom in various liver disorders, in particularly those with cholestatic features. This review summarizes epidemiology, pathophysiology, evidence-based therapeutic recommendations and currently investigated drugs for pruritus in hepatobiliary disorders. Recent Findings: Recent epidemiological data suggest pruritus as a common and relevant symptom in immune-mediated liver diseases, i.e., primary biliary cholangitis (PBC) with over 70% affected patients, up to 56% suffering from chronic pruritus. The better pathophysiological understanding of hepatic pruritus has led to the identification of novel therapeutic targets, addressed in drug trials using KOR agonists, PPAR agonists, and ileal bile acid transporter inhibitors. Summary: Hepatic itch remains among the most agonizing symptoms for affected patients and a clinical challenge for physicians. Therapeutic recommendations include a guideline-based stepwise approach starting with cholestyramine, followed by rifampicin, naltrexone, and sertraline. Bezafibrate and ileal bile acid transporter inhibitors represent promising future anti-pruritic treatment options.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Autotaxin; Bile salt; Cholestasis; Liver; Lysophosphatidic acid; Pruritus